Investigating the conditions for the effectiveness of nudging: Cue-to-action nudging increases familiar vegetable choice. (January 2019) - Broers, V.J.V.; Van den Broucke, S.; Taverne, C.; Luminet, O.
Highlights: Cue-to-action messages on tray liners increase familiar vegetable choice in general. Cue-to-action messages (type-2 nudge) decrease unfamiliar, prebiotic vegetable choice. Combined type-1 and type-2 nudge does not change prebiotic vegetable choice. Effectiveness of nudging depends on specificity and/or familiarity of products. Abstract: Inulin-type fructans (ITF), which are fibres found in vegetables such as salsify, artichoke and Jerusalem artichoke, are known for their prebiotic capacities and may contribute to preventing obesity. The current study aimed to assess the differential effects of a type-2 and a combined type-1 and -2 nudge to increase the choice for "prebiotic" vegetables at a hot vegetable buffet of a university restaurant, using a nonrandomized intervention study design involving two interventions during five consecutive weeks. An intervention was implemented in which customers were exposed to type-2 nudging in the form of short "cue-to-action" messages placed on their trays and above the hot vegetable buffet, and an additional type-1 nudging intervention was implemented in the form of placing dishes with "prebiotic" vegetables in a more accessible place. On average, 28 servings of hot vegetables were registered on a total of 503 meals sold at the restaurant per day. The beta regression model showed that the "cue-to-action" intervention increased the proportion of customers who used the hot vegetable buffet ( p < . 001, OR: 1.24), but that the proportion of "prebiotic" vegetables chosen decreased during the "cue-to-action" intervention weeks ( p < . 01, OR: 0.73). The cue-to-action intervention increased familiar vegetable choice in general and decreased unfamiliar prebiotic vegetable choice. The additional intervention of increasing the accessibility did not change prebiotic vegetable choice. The effectiveness of nudging seems to depend on the specificity and/or the familiarity of the nudged products.